2015
DOI: 10.1590/1516-1439.031415
|View full text |Cite
|
Sign up to set email alerts
|

Production of Copper and Cobalt Aluminate Spinels and Their Application As Supports for Inulinase Immobilization

Abstract: Copper and cobalt aluminates were obtained through the use of chitosan as template. In this synthesis route, chitosan is eliminated by heating, and a porous material is produced. These oxides were used as supports for inulinase immobilization by adsorption process. Physical properties of produced particles were analyzed by X-ray diffraction (XRD) and nitrogen adsorption-desorption isotherms. Both oxides presented particles containing mesoporous characteristics and high surface area, which is desirable for appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…72,79,85 The isomers differ in oxygen content and have significantly different geometries for each cluster composition (see Figure 3(b)).The XANES spectra in this case are intensely dependent on the cluster isomers. First of all, since in this case the support itself contains oxygen, and there is a known tendency of copper to mix with alumina to form copper aluminate, [86][87][88] the oxygen content of the cluster might be vague to define. In other words, Cu binds to the support and may partially dissolve in it, making it hard to define the stoichiometry of the supported cluster itself.…”
Section: Methodsmentioning
confidence: 99%
“…72,79,85 The isomers differ in oxygen content and have significantly different geometries for each cluster composition (see Figure 3(b)).The XANES spectra in this case are intensely dependent on the cluster isomers. First of all, since in this case the support itself contains oxygen, and there is a known tendency of copper to mix with alumina to form copper aluminate, [86][87][88] the oxygen content of the cluster might be vague to define. In other words, Cu binds to the support and may partially dissolve in it, making it hard to define the stoichiometry of the supported cluster itself.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that nearly all of the main group and transition metals can be synthesized in a stable spinel structure makes it a relatively large family of compounds with manifold compositions, cation ordering, electron configurations, and valence states 9 . Owing to this large synthetic flexibility and a wide range of atomic and electronic configurations accessible within this chemical space, spinels exhibit interesting magnetic 5,10,11 , electronic 12,13 , optical 14 , and catalytic 15,16 properties useful for a diverse range of applications, including data storage 17 , high frequency electronic devices 18 , dielectrics 19 , transparent conducting oxides [20][21][22][23] , lasers 24,25 , sensing 2 , energy storage 26,27 , superconductivity 28 , and biotechnology 29 .…”
mentioning
confidence: 99%
“…For comparison purposes, ZnAl 2 O 4 surface area values of 17.3, 86, 99 and 58 m 2 g −1 were obtained by combustion, co‐precipitation, hydrothermal and sol‐gel techniques (respectively), whereas CuAl 2 O 4 surface area values found in the literature were of 10, 41 and 87 (respectively) for sol‐gel, modified sol‐gel and microwave combustion techniques. Therefore, the results revealed that the route presented in this work generates materials with a high surface area by a technically easier and simpler method, without the need for sophisticated procedures such as microwave or expensive precursors …”
Section: Resultsmentioning
confidence: 99%